Discourse perspectives on second and/or foreign language teaching and learning (Education in a competitive and globalizing world series., 2013)
Discourse can be understood as the sum of linguistic usages and metalinguistic manners about a social practice. It examines language-in-use with the help of the tools that would enable us to get a deeper understanding of what is said or unsaid. Analysis of discourse would help us understand social, cultural, psychological and academic dynamics that are interwoven in the utterances of interlocutors as they use language. This book covers a range of theoretical and applied studies on the examination of discourse in various second and foreign languages learning and teaching contexts. Basically, it.